Expression of functional mouse muscle acetylcholine receptors in Chinese hamster ovary cells - Forsayeth, JR (J Neurosci, 1990)
CHO cells were transfected with cDNAs for all 4 subunits of the mouse muscle acetylcholine receptor (AChR) to obtain a stable cell line (CHO- AR) expressing the AChR on its surface. Immunoprecipitation experiments established that the AChR contained alpha- and beta-subunits assembled with gamma- and/or delta-subunits. In addition, one of the toxin- binding sites of the AChR was blocked by a myasthenic serum that specifically recognizes AChR containing the gamma-subunit. AChR from the CHO-AR cells had the same sedimentation rate, association rate constant for the binding of alpha-bungarotoxin (alpha BTX), and the same metabolic half-life as the AChR in myotubes of the mouse muscle cell line C2C12. Electrophysiological assay of CHO-AR cells by single- channel recording showed the presence of ACh-responsive ion channels with the characteristics of the embryonic AChR (gamma = 40 pS, tau = 5.6 msec). In some patches a smaller conductance channel was also seen that may represent partially assembled receptor. Fluorescence microscopy of fixed, permeabilized cells stained with rhodamine-alpha- BTX demonstrated both perinuclear and diffuse surface staining. The expression of fully assembled, functional mammalian muscle AChR in nonmuscle cells will allow detailed investigation of its properties and interactions with other cellular components.